A stubble-jumper in striped pants : memoirs of a prairie diplomat - Drake, Earl (University of Toronto Press, 1999)
Humorous, sharply written, and frank, the events recounted in these recollections include a first-hand account of the growing depth and complexity of Canada?s postwar relations with Asia.